A new approach to overcoming resistance to immunotherapy: nanotechnology - Shao, Jiangbo; Jin, Ying; Jin, Chunxiang (Frontiers in Oncology, 2023)
Immunotherapy for immune response has ushered in a new era of cancer treatment. In recent years, new immunotherapeutic agents have been introduced into clinical trials and even approved for marketing. However, the widespread use of immunotherapeutic agents faces an unavoidable challenge: immunotherapy does not work at all for some patients, or has good efficacy in the initial phase, but immunotherapy resistance develops within a short period of time, and immunotherapy can also cause serious adverse effects such as autoimmune inflammation and non-specific inflammation. How to enable patients to overcome drug resistance, reduce the toxic side effects of drugs, enhance patient compliance and improve patient survival has become a problem that clinicians have to face. The advent of nanotechnology provides an encouraging platform for immunotherapy. It can not only improve the bioavailability and stability of drugs and reduce toxic side effects, but also reduce resistance to immunotherapy. Here, we discuss these research advances and discuss potential challenges and future directions.